2006
DOI: 10.2165/00148581-200608060-00003
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the Use of Methotrexate in Juvenile Idiopathic Arthritis

Abstract: Juvenile idiopathic arthritis (JIA) is one of the most common rheumatic diseases in childhood. In a significant number of JIA cases the disease is resistant to therapy with NSAIDs, intra-articular corticosteroid injections, and physiotherapy, and methotrexate is used as a second-line agent. The efficacy of methotrexate therapy in children with JIA has been demonstrated in prospective controlled trials and this agent appears to have slightly superior efficacy compared with leflunomide. Data from randomized stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 67 publications
0
24
0
4
Order By: Relevance
“…In the present work, we have provided data on the activity of MTX against field isolates. MTX is active, with a median IC 50 (18,38). At this dose, MTX is safe and well tolerated and can yield MTX concentrations around 250 to 950 nM (15,17).…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we have provided data on the activity of MTX against field isolates. MTX is active, with a median IC 50 (18,38). At this dose, MTX is safe and well tolerated and can yield MTX concentrations around 250 to 950 nM (15,17).…”
Section: Discussionmentioning
confidence: 99%
“…This dose can yield serum concentrations of >1000 μM, a concentration range associated with MTX life-threatening toxicity [11]. By contrast, a 1000-fold lower dose of MTX (LD-MTX) [0.1-0.4 mg/kg (7.5-30 mg per adult)] is used once weekly in the treatment of rheumatoid arthritis (RA), juvenile idiopathic arthritis (JIA) in children (including infants <one year old) and psoriasis [12-14]. This use of LD-MTX is relatively safe and well tolerated, and children tolerate it better than adults [14].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, a 1000-fold lower dose of MTX (LD-MTX) [0.1-0.4 mg/kg (7.5-30 mg per adult)] is used once weekly in the treatment of rheumatoid arthritis (RA), juvenile idiopathic arthritis (JIA) in children (including infants <one year old) and psoriasis [12-14]. This use of LD-MTX is relatively safe and well tolerated, and children tolerate it better than adults [14]. Pharmacokinetic data indicate that LD-MTX yields in vivo concentrations >250 nM, which can clear malaria parasites in vivo (MTX IC 99 of 200-400 nM) [15-17].…”
Section: Introductionmentioning
confidence: 99%
“…Although evidence is limited for enhanced efficacy, some have advocated dose increases up to 25 mg/m 2 subcutaneously if necessary. 25 A randomized, controlled trial found that 30 mg/m 2 was no more effective than 15 mg/m 2 . 28 Methotrexate can be given orally, intramuscularly, or subcutaneously.…”
Section: Drug Therapymentioning
confidence: 99%